Topics in modal analysis & testing. proceedings of the 36th IMAC, a Conference and Exposition on Structural Dynamics 2018 /: proceedings of the 36th IMAC, a Conference and Exposition on Structural Dynamics 2018. Volume 9 : ([2019]) - Unknown
No abstract available